P109 Rifaximin and Saccharomyces boulardii increase stress resilience in TNBS-induced colitis. (16th January 2018) - Konturek, P; Zopf, Y; Dieterich, W; Wirtz, S; Neurath, M F; Brzozowski, T
Abstract: Background: Inflammatory bowel disease (IBD) is a multi-factorial systemic disorder which involves immune, genetic and environmental factors. Stress, in its various forms, plays an important role in the pathogenesis of IBD and is responsible for the induction of acute exacerbations of colitis. Moreover, stress increases the gut barrier permeability and has negative impact on gut microbiota composition. The measures which reduce stress should help control symptoms and activity of IBD. Methods: In the present study, Wistar rats were exposed three times to short water immersion and restrain stress (WRS for 30 min) during 7 days before induction of colitis. In the next step, TNBS- colitis was induced. Rats with colitis were assigned to three treatment groups: (1) vehicle, (2) Saccharomyces boulardii (750 mg/day i.g. ) or (3) antibiotic rifaximin (100 mg /kg daily i.g.). 9 days after induction of colitis, the animals were sacrificed, and lesion index and colonic blood flow (using H2 gas clearance method) were measured. Additionally, the plasma level of proinflammatory cytokines such as TNFa and IL1b was measured by ELISA. Finally, the fecal microbiota composition was assessed by 16S RNA sequencing analysis. Results: Rats with colitis and exposed to stress showed a significantly increased area of colonic lesions and decrease in colonic blood flow (CBF) as compared with rats with TNBS colitis without stress exposure. Both, S. boulardii and rifaximin decreased the area of colonic lesions and significantly increased CBF. The highest level of IL1b and TNFa was observed in rats with colitis and exposed to stress, but the treatment with S. boulardii or rifaximin significantly reduced their level. As compared with vehicle treated group, rats with experimental colitis showed an increased abundance of Prevotellaceae, Porphomonadaceae and reduction in Clostridiaceae, Lachnospiraceae. Lactobacillaceae, Oscillospiraceae, and Eubacteriaceae. In rats with colitis and exposed to stress, further increase in Prevotellaceae and decrease in Clostridiaceae, Lachnospiraceae. Lactobacillaceae, Oscillospiraceae, and Eubacteriaceae was observed. Conclusions: Exposure to stress aggravates TNBS-colitis and has negative effects on gut microbiota composition. Modulation of gut microbiota by rifaximin or S. boulardii increases stress resilience in rats with experimentally induced colitis.